HUBUNGAN ANTARA IKLIM ORGANISASI DENGAN SUBJECTIVE WELL-BEING PADA KARYAWAN DI PERUSAHAAN X - Hartanto, Erlinda Wongso; Kurniawan, Jimmy Ellya (Jurnal Psikologi Teori dan Terapan, 2015)
Subjective well being (SWB) is one of important thing in humanâs life because it may correlate with higher productivity and a good social relationship. SWB isÂ individualâs evaluation of their experience for the whole picture or each domain of life including their satisfaction and feeling. For adult, work domain take most of the time each day. That is why situation at work might affect their evaluation. Evaluation atÂ working situation called organizational climate. The aim of this paper is to investigateÂ the correlation between organizational climate and subjective well being among employees. This study utilized quantitative approach with correlational design. Total number of the subject was 63 employees from X company who were selected using Â population cluster sampling technique. Data collection tool was adapted from LSOCQ, SWLS and SPANE. Result showed that there was a positive correlation betweenÂ organizational climate and subjective well-being among X companyâs employees (r = 0.623, p = 0.000; r = 0.434, p = 0.000). Finding showed that employee who work in a good organization climate have a good subjective well-being. Finding also show that gender, age, income, status and education were believed to have a correlation with SWB on employees.Abstrak: Subjective well being (SWB) adalah hal penting yang ingin dicapai dalam kehidupan karena dapat meningkatkan produktivitas dan hubungan sosial yang baik. SWB merupakan evaluasi kepuasan dan afeksi individu terhadap pengalaman hidup mereka baik secara keseluruhan maupun per domain kehidupan. Domain yang memakan waktu paling banyak dalam kehidupan manusia dewasa adalah domain kerja. Evaluasi individu terhadap domain pekerjaannya disebut iklim organisasi. Oleh karena itu diduga bahwa iklim organisasi dapat mempengaruhi tingkat SWB karyawan. Tujuan dari penelitian ini adalah mengetahui hubungan antara iklim organisasi dengan SWB karyawan. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasian. Subjek terdiri dari 63 karyawan perusahaan X dan dipilih menggunakan cluster sampling. Alat ukur iklim organisasi menggunakan LSOCQ sementara SWB menggunakan SWLS dan SPANE. Hasil menunjukan ada korelasi positif antara iklim organisasi dengan SWB (r = 0.623, p = 0.000 ; r = 0.434, p= 0.000). semakin baik iklim di suatu organisasi maka semakin tinggi SWB karyawan dan begitu sebaliknya.